Oxidation of Lingwu Coal Extraction Residue in Aqueous Sodium Hypochlorite under Mild Conditions - 赵云鹏 宗志敏 李金纳 王月伦 樊星 魏贤勇 (Transactions of Tianjin University, 2015)
To investigate the structural features and provide an alternative method for high value-added utilization of coal, Lingwu coal was first extracted with organic solvent at room temperature. Then its extraction residue was oxidized in aqueous sodium hypochlorite （ASHC） under mild conditions. The effects of oxidation conditions, such as temperature, reaction time, the ratio of Lingwu coal extraction residue （LCER, g） to ASHC （mL） and pH value, on the product distributions and compositions were investigated. The results of gas chromatography/mass spectrometry （GC/MS） suggested that 53 kinds of methyl esterified products were detected in total, and benzene carboxylic acids were the main oxidation products, while chloro-substituted benzene carboxylic acids were the main by-products. Higher yield and fewer kinds of organic acids could be obtained at lower pH value, especially for the main objective product, benzene carboxylic acids.